Drawing 100 years of Disney wonder : [a retrospective collection of artwork featuring iconic Disney characters from the past 100 years] - Fanning, Jim; Deja, Andreas, 1957- (Walter Foster Publishing, an imprint of The Quarto Group, 2023)
Spotlighting 100 characters from the 1920s to the 2020s, this book features vintage and modern illustrations from The Walt Disney Company and Andreas Deja's personal archives, as well as essays exploring the history of Disney animation. You can re-create and draw the best of Disney's characters while celebrating the Disney design process, character evolutions, and artist interpretations.-- From back cover.